PKS J0805-0111: A Second Owens Valley Radio Observatory Blazar Showing Highly Significant Sinusoidal Radio Variability—The Tip of the Iceberg - de la Parra, P. V.; Kiehlmann, S.; Mroz, P.; Readhead, A. C. S.; Synani, A.; Begelman, M. C.; Blandford, R. D.; Ding, Y.; Harrison, F.; Liodakis, I.; Max-Moerbeck, W.; Pavlidou, V.; et al. (American Astronomical Society, 2026)
Owens Valley Radio Observatory observations of the supermassive black hole binary (SMBHB) candidate PKS 2131-021 revealed, for the first time, six likely characteristics of the phenomenology exhibited by SMBHBs in blazars, of which the most unexpected and critical is sinusoidal flux density variations. We have now identified a second blazar, PKS J0805-0111, showing similar variations, with a period of 1.422 +/- 0.005 yr in the rest frame of the z = 1.388 object. PKS J0805-0111 displays five of the six characteristics observed in PKS 2131-021. To estimate the significance of the sinusoidal variations, we generate 106 simulated light curves that reproduce the radio variability characteristics of PKS J0805-0111 and show that the global probability that the periodicity we detect is due to the red-noise tail of the power spectral density is p = 6.7 x 10-5 (3.82 sigma). This shows that PKS 2131-021 is not a unique case. The discovery of these two objects in a sample of 1158 blazars allows us to reject, at a p-value similar to 0.003, the null hypothesis that the sinusoidal variations in these two blazars are all due to a red-noise process. We estimate that the number of SMBHB candidates among blazars is similar to 1 in 100.